Riverine flood mitigation in Masantol, Pampanga - Serrano, Jonathan S.; Villalba, Imee Bren O. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
This study aims to assess the flooding in Masantol, a mlLllicipality in Pampanga, by creating a flood model using LISFLOOD-FP and HEC-RAS. Masantol is located near Manila Bay which is the outlet of the Pampanga River Basin, hence flooding in the place is severe. Using 1OO yr-RIDF data, corresponding RIDF-calibrated flows in Arayat, 30-m DTM, and an estimated Manning's n from land cover maps, a 4-day simulation was run in LISFLOOD. The model covers the floodplain from Arayat up to a diversion from the main channel in Apalit, Pampanga where the results from LISFLOOD remained stable. The outflow hydrograph obtained from the simulation has a peak of 2736.7 cms at the 68th hour. This was then used in HEC-RAS to route the river upto the reaches in Masantol, with Sapang Maragol as a critical reach since it is beside the town proper. Levees were then designed in HEC-RAS at a stage of 4.5 m and maximum water stages were compared for the model with and without levees to see if there is a significant increase in water stages. Results show that levees caused minor increase in upstream areas and only caused signjficant increase in a downstream reach which was far from the town proper. Other cases were also done such as the comparison of 50-yr and 100-yr flood scenarios, not including rainfall in the LISFLOOD model, and inclusion of the Angat River, a main tributary of Pampanga River, in the HEC-RAS model.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Hydrologic models; Flood damage prevention -- Philippines -- Pampanga